Prevalence and Antifungal Susceptibility Pattern of Candida species Isolated from Patients with Urinary Tract Infections - Osinupebi AO; Adeosun OV; Lawal IA (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2021)
Background: The presence of Candida species in the urine is termed candiduria, and it is a common form of urinary tract infection (UTI). Many other species of Candida organism apart from Candida albicans are known with increasing the occurrence of resistance to available antifungal agents. Objectives: To determine the prevalence and sensitivity pattern of Candida isolates obtained from urine samples of diagnosed urinary tract infections. Methods: Midstream urine of patients attending the Lagos University Teaching Hospital, Ikeja Lagos, were collected and inoculated on Sabouraud Dextrose Agar (SDA). Microbiological processing was done with Gram reaction, germ tube test, CHROME agar TM and sugar fermentation test using API 32C system. Antifungal susceptibility tests were done using the agar disc diffusion method. Results: Candida species were obtained from 36 (12.9%) of 280 patients with UTI. Candida albicans (CA) had the highest frequency (12; 33.3%) compared to 24 (66.7%) for Non-albicans Candida (NAC). The speciation of Candida using Chrome Agar showed some misidentification from the API32C identification, but there was a significant correlation between API32C and Chrome Agar methods (r = 0. 9793). Half of the C. albicans species were sensitive to fluconazole while C. hellenica was only sensitive to Nystatin. The C. parapsilopsis had the highest susceptibility pattern, with 86% and 71% for fluconazole and ketoconazole, respectively. Generally, ketoconazole had the highest effectiveness on Candida species. Conclusion: This study demonstrated the role of Candida species in UTIs and their high susceptibility to ketoconazole.